Development of Generalized Model of 3-Phase Induction Motor for Performance Study During Different Distorted and Unbalance Voltage - Thakur, Arunava Kabiraj; Das, Arabinda; Kundu, Palash Kumar (International Journal of Computer Sciences and Engineering, 2020)
Due to the introduction of FACT devices in power supply system and complicated control in power industry, presence of harmonics in power supply system is a common problem. It increases day by day and it distorts and unbalances the supply voltage. Due to unequal transformer tap settings, open delta connected transformer banks, unbalanced distribution of single phase loads supply voltage unbalance may occurs. Three phase induction motor is the main workhouse of modern industries. Due to the application of such a polluted supply voltage the performance of three phase induction motor may be affected seriously and this may affect the load connected with the drive system. To take correct measure during torque and speed control, it is required to know the performance during voltage unbalance and distorted supply due to different harmonics. To mitigate this, an attempt has been made to develop a generalized model of a three phase induction motor for online performance study of torque and speed during different distorted and unbalance supply voltage. In doing this, Matlab/Simulink has been used to develop a model based on generalized theory of induction motor. Finally, using the model, performance has been studied during application of different distorted and unbalanced supply and reported.